2021
DOI: 10.1108/bij-09-2021-0514
|View full text |Cite
|
Sign up to set email alerts
|

Building resilience in retail supply chains: Lessons learned from COVID-19 and future pathways

Abstract: PurposeThis study explores the countermeasures taken by retailers to mitigate the effects of COVID-19 on supply chain disruptions.Design/methodology/approachThis research uses a multiple case study approach and undertakes 36 semi-structured interviews with senior management of the four largest retailers of the United Arab Emirates. The respondents were designated at different positions such as Vice President, Director and Project Manager.FindingsResults reveal that retailers are employing six countermeasures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 85 publications
1
13
0
2
Order By: Relevance
“…This study contributes to the literature on the FMCDM continuous improvement applications. Our findings extend those of previous studies, such as those of Butt (2021), who discussed resilience in the retail supply chain and lessons learned from COVID-19. Researchers who seek causal relationships analysis can build on our DEMATEL analysis results to examine the influence metrics deeply.…”
Section: Theoretical Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…This study contributes to the literature on the FMCDM continuous improvement applications. Our findings extend those of previous studies, such as those of Butt (2021), who discussed resilience in the retail supply chain and lessons learned from COVID-19. Researchers who seek causal relationships analysis can build on our DEMATEL analysis results to examine the influence metrics deeply.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…This study contributes to the previous research on resilience management (Butt, 2021;Jain et al, 2021;. Recent studies show the importance of resilience during the post-COVID-19 period for supply chain management (Golan et al, 2020;Ivanov, 2020;Ivanov and Dolgui, 2020;Remko, 2020).…”
Section: Introductionmentioning
confidence: 54%
“…In recent studies on the global supply chain, manufacturing firms have reported many adverse supply chain disruptions due to the COVID-19 outbreak, which has unfolded as a "black swan" according to the experts (Butt, 2021;Ketchen Jr and Craighead, 2020;Betcheva et al, 2020). The supply chain disruptions caused by this pandemic have shuttered region, national as well as global economies.…”
Section: Risk Management Of Supply Chains 253mentioning
confidence: 99%
“…Sarkis et al (2020) and Sato et al (2020) proposed two major categories of SCR: operational risks (demand, supply and cost) and disruption risks (man-made, economic or natural disasters). When viewed from a different perspective, SCR can be classified along quantitative and qualitative lines under eight risk categories: demand, supply, operational, resource, competitive, security, macro and policy (Butt, 2021;Munir et al, 2020;Baryannis et al, 2019). SCR can also be classified into three further categories: environmental risks, network risks and organizational risks (Sarkis, 2021;Ivanov et al, 2019).…”
Section: Underpinning Elements 21 Supply Chain Risk Managementmentioning
confidence: 99%
“…Similarly, the COVID-19 is hitting firms hard and adversely affecting firms’ operations, greatly reducing their profits. For example, German Post announced an EBIT reduction of between EUR 60 million and EUR 70 million; China’s retail prices increased by an average of 21.9% in February 2020 (Bild, 2020; Butt, 2021e). Apple reported a fall in its quarterly earnings on 17 February (Apple, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%